The investigation of Structural and Magnetic Properties of Lanthanum and Barium Located into Multiferroic Ferrite Bismuth Nanoparticles in the Presence of Sugar Based Natural Surfactants Using Coprecipitation Approach - Mohammadhossein Farghadin; Reza Derakhshandeh-Haghighi; Navid Hosseinabadi; esmaeil jafari (مواد نوین, 2021)
Nanoparticles are comprised from dozens or hundreds of atoms or molecules with different sizes and morphologies are being applied widely due to their unique properties in chemistry, physic, and biology. Multiferroic compounds have been considered significantly owing to their applications arising from their ferromagnetic, ferroelectric, and fibroelastic properties. Among all multiferroic compounds, ferrite bismuth (BiFeO3) has attracted remarkable attentions which is a weak pad-ferromagnetic in the magnetic points of view. Of the best impressive approaches for improving its properties is the substitution of the metals including La, Ba, Pd, Sr, and Ca in A positions or Ti, Cr, and Mn in B positions through BiFeO3 scaffold. In this work, Bi1-XLaxFeO3 and Bi0.9-YLa0.1BaYFeO3 nanoparticles were synthesized and the structural and magnetic properties of synthesized nanoparticles were also studied.BiFeO3 particles were synthesized by mixing the Bi(NO3)3.5H2O, La(NO3)2.6H2O, Ba(NO3)2.4H2O, and Fe(NO3)3.9H2O precursors in nitric acid in the presence of surfactants Saponin, Triton CG-100, Crocin, or N-octyl-beta-D-glucoside and tetraethylenepentamine as base.